2011
DOI: 10.1111/j.1471-4159.2010.07162.x
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium‐induced oxidative stress triggers endoplasmic reticulum stress in rat cortical neurons

Abstract: J. Neurochem. (2011) 117, 38–47. Abstract Introduction of Gadolinium (Gd) to the nervous system is linked to the development of neurotoxicity involving both oxidative and endoplasmic reticulum (ER) stress. Gd levels (0.2–20 μm) in the form of gadolinium trichloride (GdCl3) cause neurotoxicity in vitro. We investigated the signaling pathways in primary cultured rat cortical neurons and tested whether GdCl3 induced oxidative and ER stress. Results showed that Gd‐induced neural cell death followed a rapid accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 52 publications
4
60
0
5
Order By: Relevance
“…This result was possibly attributable to neurotoxicity induced by gadolinium used as contrast. Gadolinium, a rare-earth lanthanide metal, has been shown efficient in provoking impaired mitochondrial function and oxidative stress (Feng et al 2010) and able to trigger endoplasmic reticulum stress-related signal transduction in rat cortical neurons (Xia et al 2011). Due to some important limitations of MRI findings in MS, such as the poor correlation with clinical disability, we suggest that use of gadolinium can be limited to first diagnostic neuro-imaging (Sicotte 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This result was possibly attributable to neurotoxicity induced by gadolinium used as contrast. Gadolinium, a rare-earth lanthanide metal, has been shown efficient in provoking impaired mitochondrial function and oxidative stress (Feng et al 2010) and able to trigger endoplasmic reticulum stress-related signal transduction in rat cortical neurons (Xia et al 2011). Due to some important limitations of MRI findings in MS, such as the poor correlation with clinical disability, we suggest that use of gadolinium can be limited to first diagnostic neuro-imaging (Sicotte 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the dentate nucleus and globus pallidus have shown significantly higher Gd accumulation than other brain regions (2, 12). Moreover, Gd induces cell death by inhibiting mitochondrial function and by inducing oxidative stress, followed by a rapid accumulation of reactive oxygen in primary cultures of rat cortical neurons (13, 14). By contrast, another study showed that administration of GBCAs does not cause any severe neurological alterations, such as seizures (15).…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al [14] have also showed that disturbance in endoplasmic reticulum (ER) function plays an important role in neuronal pathogenesis. ER is responsible for the proper folding and sorting of proteins and involve proteasome pathway.…”
Section: Introductionmentioning
confidence: 99%